Political Opportunity, Media Framing and Resource Mobilization: A Study on Social Protest Against Indonesia Regional Election Law Revisions - Fanda Amalia Putri (Political Sciences Program Study, 2024)
This article discusses social movement in the case of regional election law revision that held on 2024. This article use three main theoritical perspectives they are political opportunity structure, media framing, and resource mobilization. The background of the social movement began with public concerns about the House of Representative’s decision that contradicted with Constitutional Court's decision regarding the regional election law revision. This is considered to threaten the democracy principles. The House of Representative is considered to perpetuate certain political interests by ignoring the decision which is seen as final and binding. This study uses a qualitative method. Data were obtained through observation and media report. The analysis is carried out by comparing data from various sources to ensure the accuracy of the information. The results of the study show that the social movement conducted is success because it is conditioned by several key factors. In the theory of political opportunity structure, this movement received any supports from several political elites, especially from the Indonesia Democratic Party (PDIP), that rejected the issue of regional election law revision. In the perspective of media framing, this movement succeeded in mobilizing masses with narration of